The Influence Of Profitability And Corporate Social Responsibility On Company Value (Study On Mining Companies Listed On The Indonesian Stock Exchange (IDX) 2018-2023) - R. Enough Bhaktiar; Dendi Hermawan (Jurnal Scientia, 2024)
The aim of this research is to examine and analyze the influence of profitability and corporate social responsibility on company value in Food and Beverage Companies listed on the Indonesia Stock Exchange in 2018-2023. Profitability uses return on assets and corporate social responsibility is measured using CSDI. The total sample used in this research was 18 companies through purposive sampling. The data used in this research is secondary data. To test the hypothesis in this research, the multiple linear regression analysis method was used with a significance level of 0.05 using SPSS. The coefficient of determination result in this research is 40.3% which can be explained by the independent variables, namely profitability and corporate social responsibility on the company value variable. The results of this research show that profitability influences company value, corporate social responsibility influences company value. profitability, and corporate social responsibility simultaneously influence the company value of mining companies listed on the Indonesia Stock Exchange (BEI). Because the significance level is <0.05.